2018
DOI: 10.2174/1871527317666180720162029
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic Lateral Sclerosis and Oxidative Stress: A Double-Blind Therapeutic Trial After Curcumin Supplementation

Abstract: Although further studies are needed to confirm these data, treatment with curcumin shows encouraging results indicating a slight slowdown in disease progression, improving aerobic metabolism and oxidative damage, this also contributing to deepen knowledge into the pathogenic mechanisms of ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 34 publications
0
59
0
Order By: Relevance
“…The most promising phytochemical, curcumin has a protective role in ALS too. It acts for mitochondrial biogenesis leading the AMP/PGC-1α and/or Nfr2 pathway [83]. The clinical studies show the effectiveness of curcumin for slowing down the progress of the disease.…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…The most promising phytochemical, curcumin has a protective role in ALS too. It acts for mitochondrial biogenesis leading the AMP/PGC-1α and/or Nfr2 pathway [83]. The clinical studies show the effectiveness of curcumin for slowing down the progress of the disease.…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Curcumin helps in the improvement of aerobic metabolism and oxidative stress. The antioxidative mechanism is responsible for leading the protective effect against ALS [83]. A studied phytochemical named withaferin A shows an anti-inflammatory effect by working as antagonistic of NF-κB and is found to be effective for the improved motor activity in transgenic mice model [84].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Curcumin may improve survival in patients with ALS, especially those with bulbar involvement (Ahmadi et al, 2018). In a double-blind therapeutic trial, treatment with curcumin showed a decrease in ALS progression and a reduction of oxidative damage (Chico et al, 2018) (Table 1).…”
Section: Curcuminmentioning
confidence: 99%
“…To our knowledge, only two studies that evaluated the exercise-induced oxidative stress remodulation in ALS have been conducted in humans (Pasquinelli et al, 2016;Chico et al, 2018). In both studies, the exercise protocol, on the forearm muscles with a myometer, consisted in several steps in which the contractile force increased incrementally at 30, 50, and 70% of the MVC, each step including 1 min of intermittent contractions (∼1/s) and 2 min of rest.…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…In the second study, Chico et al (2018) evaluated, over a period of 6-month trial and compared to clinical scores, the exercise-related effects, on the same redox parameters, of the oral administration of a curcumin-based compound (600 mg/day, Brainoil), a natural antioxidant nutraceutical, in ALS patients. Patients were randomized into two groups: group A (n = 24) received placebo for 3 months, then Brainoil for the following 3 months; group B (n = 18) took Brainoil for 6 months.…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%